Craft in the Digital Era: Louis Sullivan, Digital Technology, and Designbuild Education - Keith Van de Riet (Oz, 2017)
Perhaps digital craft in architecture can be effectively calibrated through emulation of the masters. This is not to suggest we retrogress to periods of architectural style, but rather leverage relevant benchmarks within pedagogical models to establish standards of craft in digital design and fabrication. By adopting this preservation-oriented and Beaux- Arts style of learning, computational technologies can be vetted through the modeling and construction of architecture embedded with some of the most recognized achievements of human hand and mind.